Plataforma computacional sobre Amazon Web Services (Aws) de renderizado distribuido - Rojas-Albarracín, Gabriel; Páramo-Fonseca, Jorge; Hernández-Merchán, Cindy (Revista Científica, 2017)
Today has created a dynamic in which people require higher image quality in different media formats (games, movies, animations). Further definition usually requires image processing larger; this brings the need for increased computing power. This paper presents a case study in which the implementation of a low-cost platform on the Amazon cloud for parallel processing of images and animation.